Topology of Minimal Walking Technicolor - Biagio Lucini (The European Physical Journal C, 2013)
We perform a lattice study of the topological susceptibility and instanton size distribution of the SU(2) gauge theory with two adjoint Dirac fermions (also known as Minimal Walking Technicolor), which is known to be in the conformal window. In the theory deformed with a small mass term, by drawing a comparison with the pure gauge theory, we find that topological observables are decoupled from the fermion dynamics. This provides further evidence for the infrared conformality of the theory. A study of the instanton size distribution shows that this quantity can be used to detect the onset of finite size effects.